2021
DOI: 10.1111/trf.16660
|View full text |Cite
|
Sign up to set email alerts
|

Prozone rates in the solid‐phase platelet crossmatch assay and correlation with class I HLA antibody levels

Abstract: Background Solid‐phase platelet crossmatch (PXM) testing is used to help manage patients with platelet transfusion‐refractoriness. Recently, we published the first report of false‐negative PXM results from prozone effect that was mitigated using sample dilution. This study aimed to describe the prevalence of PXM prozone effect and the levels of class I HLA antibodies (HLA‐Abs) associated with positive PXM results and with false‐negative PXM results from prozone effect. Study Design and Methods A cross‐sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…17 However, on a follow up study from the same group, the authors examined a cohort of 59 PR patients undergoing PXM and concluded that maximum mean fluorescence intensity (MFI) and MFI sum (an arguable surrogate for antibody titer) on solid-phase HLA testing were not predictors of the prozone effect. 18 Nonetheless, out of 830 ABO-compatible PXMs, they found a false-negative rate of ~5% attributable to prozone. Thus, prozone effect in PXM appears to be a rather common occurrence with an underlying mechanism that remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…17 However, on a follow up study from the same group, the authors examined a cohort of 59 PR patients undergoing PXM and concluded that maximum mean fluorescence intensity (MFI) and MFI sum (an arguable surrogate for antibody titer) on solid-phase HLA testing were not predictors of the prozone effect. 18 Nonetheless, out of 830 ABO-compatible PXMs, they found a false-negative rate of ~5% attributable to prozone. Thus, prozone effect in PXM appears to be a rather common occurrence with an underlying mechanism that remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…Horton et al presented a case of false‐negative solid phase PXM and postulated that the mechanism is more likely to be classic prozone 17 . However, on a follow up study from the same group, the authors examined a cohort of 59 PR patients undergoing PXM and concluded that maximum mean fluorescence intensity (MFI) and MFI sum (an arguable surrogate for antibody titer) on solid‐phase HLA testing were not predictors of the prozone effect 18 . Nonetheless, out of 830 ABO‐compatible PXMs, they found a false‐negative rate of ~5% attributable to prozone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations